Fabrication of 3D microfeatures on thin metal foils using laser-induced shock pressure - Nagarajan, Balasubramanian (2015)
The increasing demand in the metallic microfabrication in recent times highlights the significance of microforming process due to its compliance with mass production, customization, materials, and formability. Nevertheless, the existing microforming processes are limited by a number of factors including fabrication of micromolds/punches, friction and wear of contact surfaces, size effects, and process flexibility. This thesis attempts to address these limitations by developing a new microforming process for fabricating 3D microfeatures on metallic foils. A novel mold-free microforming technique, Flexible Pad Laser Shock Forming (FPLSF), which uses laser-induced shock pressure and a flexible pad to fabricate microscale features on metal foils is developed and demonstrated. FPLSF uses laser-induced shockwaves as the deformation force to induce plastic deformation on metal foils, where flexible pad acts as the backing support. Hemispherical microcraters of depth ~ 15 μm to 300 μm and radius ~ 150 μm to 1 mm with excellent surface quality are produced on copper, nickel, and stainless steel foils (25 μm thickness). The formed features experience beneficial uniform thickness distribution and material strengthening. In order to understand the effect of various process parameters on foil deformation characteristics, a detailed parametric study is performed. The process parameters include laser fluence, number of pulses, laser system, ablative overlay, ablative overlay thickness, confinement medium, confinement thickness, flexible pad material and its thickness. The correlations between the process variables and deformation features are established. As FPLSF is a new process, it is necessary to understand the process mechanisms involved. In FPLSF, the principle mechanism behind laser-induced shock pressure is the formation and propagation of plasma upon laser irradiation. Therefore, a detailed investigation of laser-induced plasma characteristics is carried out using a high speed camera. The plasma lifetime and plasma expansion during FPLSF are studied initially. Moreover, the effects of laser fluence, number of pulses, confinement medium, and confinement thickness on the plasma characteristics are analyzed and correlated with the corresponding plastic deformation of metal foils. FPLSF is a high-strain rate forming process involving strain rates of 105 s−1, where the deformation mechanisms are possibly influenced by high-strain rate effects. To study the underlying plastic deformation mechanism during FPLSF, mechanical properties and microstructure of copper foil are studied. Initially, thickness distribution of the deformed foils along the cross section at different positions is examined. Hardnesses at the cross-section, top surface, and bottom surface of the crater are examined subsequently. The microstructure variation on copper foil surfaces due to FPLSF is investigated using Electron BackScatter Diffraction (EBSD) technique. The microstructure of the foil is characterized using grain size distribution, grain boundary misorientation angle, and texture. Strain hardening is identified to be the prominent plastic deformation mechanism in FPLSF rather than the typical adiabatic softening effect known to be occurring at high strain rates for processes such as electromagnetic forming, explosive forming, and laser dynamic forming. This significant difference in deformation mechanism with FPLSF is attributed to the concurrent reduction in plastic strain, strain rate and the inertia effects, resulting from the FPLSF process configuration. Finally, finite element analysis (FEA) of FPLSF is performed to study the deformation characteristics of metal foil and flexible pad. A 3D finite element model is developed to simulate the high strain rate plastic deformation of metal foil and hyperelastic deformation of flexible pad in the commercial FE package, ABAQUS. FE model is validated first by comparing the shape, depth, and diameter of the deformation features between experiments and simulation. A time-resolved analysis of stress and strain distributions at different positions along the foil is carried out. The stress-strain distributions are correlated with the experimental results to understand the observed process behaviors. Furthermore, several process variables, laser fluence, material and thickness of the metal foil, and flexible pad are investigated using FEA.